Regional financial system and the financial structure of small firms - Prashanth Mahagaonkar; Swayan Chaudhuri (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
The capital structure of firms is known to be different not only due to firm characteristics but also to the sources of capital. Therefore, there is a need to understand the supply side effects on a firms capital structure. A small firms choice of financing sources may be limited by the supply-side financial endowment of the region. Small firms are known to be heavily reliant on internal finance and the quantity and price channels are expected to drive usage of debt. Our findings on 2000 small firms in Eng land show that the quantity and price channels might work only for supply of very local capitals. Firms tend to prefer internal finance when semi-local or national institutions show higher commercial operational distance in their region. These results point out that semi-local and national institutions tend to drive away usage of debt due to monitoring costs or credit rationing, while very local institutions increase the usage of debt through quantity or price channels.
Keywords: G24; G32; E5; N2; O18; 330; Capital structure; regional financial system; information asymmetries; geography; Kapitalstruktur; Klein- und Mittelunternehmen; Finanzierung; Regionaler Finanzmarkt; Asymmetrische Information; England